Results and Performance of the World Bank Group 2013 : An Independent Evaluation. Volume 1. Main Report - Independent Evaluation Group (World Bank, Washington, DC, 2014)
The global extreme poverty rate has fallen by half since 1990, but progress within the developing world has been uneven. Extreme poverty remains widespread in most low-income countries while many middle-income countries also continue to have substantial levels with many people there who have escaped extreme poverty remaining poor and vulnerable. Nor has there been robust progress in sharing prosperity: in many developing countries rapid growth has been accompanied by rising inequality, often with a geographic and ethnic dimension as progress in isolated areas has lagged behind. This appendix describes select elements of the evaluation systems in the World Bank, the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA) that are the basis for this report. They illustrate commonalities as well as differences in evaluation practices across the institutions. The World Bank, IFC, and MIGA differ in the instruments and approaches they use to achieve development results. Each institution has an evaluation system tailored to its needs. In each organization, the evaluation system comprises different components, self-evaluation, independent evaluation, and validation of self-evaluation.